Analysis On Political Speech Of Susilo Bambang Yudhoyono: Common Sense Assumption And Ideology - Sayit Abdul Karim (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2015)
This paper presents an analysis on political speech of Susilo Bambang Yudhoyono (SBY), the former president of Indonesia at the Indonesian conference on â€œMoving towards sustainability: together we must create the future we wantâ€. Ideologies are closely linked to power and language because using language is the commonest form of social behavior, and the form of social behavior where we rely most on â€˜common-senseâ€™ assumptions. The objectives of this study are to discuss the common sense assumption and ideology by means of language use in SBYâ€™s political speech which is mainly grounded in Norman Faircloughâ€™s theory of language and power in critical discourse analysis. There are two main problems of analysis, namely; first, what are the common sense assumption and ideology in Susilo Bambang Yudhoyonoâ€™s political speech; and second, how do they relate to each other in the political discourse? The data used in this study was in the form of written text on â€œmoving towards sustainability: together we must create the future we wantâ€. A qualitative descriptive analysis was employed to analyze the common sense assumption and ideology in the written text of Susilo Bambang Yudhoyonoâ€™s political speech which was delivered at Riocto entro Convention Center, Rio de Janeiro on June 20, 2012. One dimension of â€˜common senseâ€™ is the meaning of words. The results showed that the common sense assumption and ideology conveyed through SBYâ€™s specific words or expressions can significantly explain how political discourse is constructed and affected by the SBYâ€™s rule and position, life experience, and power relations. He used language as a powerful social tool to present his common sense assumption and ideology to convince his audiences and fellow citizens that the future of sustainability has been an important agenda for all people.Â Â Keywords: Political speech, common sense, assumption, ideology, sustainability, growth.